E-government in the context of monitory democracy: Public participation and democratic reform - Julie Freeman (2013)
In a networked environment characterised by communicative abundance, there are new opportunities for citizens to scrutinise and contest government actions and decisions. Governments are subsequently facing increasing civic demand for greater transparency, responsiveness and accountability. This article suggests that e-government mechanisms offer contexts through which governments can respond to growing external pressures and adapt to changing notions surrounding democratic participation. It explores efforts undertaken during Iceland’s constitutional reform process, where nation-wide public involvement was encouraged through a combination of digital and traditional political participation methods. The initiative undertaken in Iceland signals a shift away from the transactional activities often associated with government use of information and communication technologies (ICTs) towards more open and responsive e-government practices. This article argues that, to be effective, civic engagement through e-government should be an ongoing process that is integrated into the everyday operations of governments to support and supplement existing democratic practices.